Injectable Tissue Replacement and Regeneration: Anatomic Fat Grafting to Restore Decayed Facial Tissues - Steven R. Cohen, MD; Hayley Womack, BS (Plastic and Reconstructive Surgery, Global Open, 2019)
Summary:. Aging is a dynamic process that can be modeled and understood tissue by tissue and cell by cell. Numerous authors have helped us understand the anatomy of facial fat compartments and the effects of aging on our facial tissues such as skin, fat, bone and fibrous ligaments. Injectable tissue replacement and regeneration (ITR2) is a method to replace decayed tissues of the face using “like tissues” in an effort to delay or slow the rate of tissue decay seen in facial aging. Facial topography and proportion analysis are performed to diagnose individual-specific losses of facial fat. The degree of sun damage and skin thinning is noted as is the degree of loss in the superficial fat compartment. Deep compartment fat loss is evaluated as is pyriform aperture, orbital, mandibular ramus, mandibular body, and chin resorption. From this analysis, a detailed treatment plan is formulated. Using a mechanical device, 3 different fat grafts are created: 2 mm (millifat), 1 mm (microfat), and 500 microns (cell optimized, matrix rich nanofat); anatomic replacement of all areas of tissue loss is carried out. Millifat is used for deep compartment and bone losses, microfat for superficial fat losses above the facial musculature and nanofat is used intradermally and as a biological cream for topical application. The rationale behind this standardized approach is explained and the scientific foundations for the idea are presented. Reduction in tissue decay appears to be a valid observation, but awaits others confirmation.